Heat transfer characteristics of two-phase thermosyphons - Кравец, Владимир Юрьевич; Чернобай, Вадим Алексеевич; Готовцева, Алёна Константиновна (Eastern-European Journal of Enterprise Technologies, 2012)
Experimental data of temperature state and heat transfer characteristics of closed two-phase thermosyphons with 3 mm and 9 mm internal diameters, 700 mm length (heat carrier-water) are presented. Specific features of heat transfer processes inside the thermosyphon associated with fluctuating phenomena are shown